Walkable City Rules 101 Steps to Making Better Places - Speck, Jeff (Island Press/Center for Resource Economics, 2018)
"Walkable City Rules is worth reading even for those of us who will never set foot in a planner's office. Like Walkable City, this book explains how a variety of laws and rules frustrate the person who wishes to get from one place to another on foot. But to a much greater extent than most books about walkability, this book tells readers what can be done to improve upon the status quo." Planetizen "A concise, updated, how-to version of [Speck's] 2012 Walkable City." 8 "Has there ever been a smarter, more illuminating, jargon-free, and deeply useful guide to making more sociable, healthy, prosperous, charming neighborhoods, towns, and cities? Every local leader and every engaged local citizen owes it to themselves to read Walkable City Rules." Kurt Andersen, author of "Fantasyland" and host of public radio's "Studio 360" "Filled with the photos, graphics, and charts that many of his fans felt were missing from the last book, the new volume comprises 1010 mini-chapters, each of which elegantly distills a single precept from his philosophy.".